Die skep en vergelyking van geometriese lêers van driedimensionele modelle - van Staden, Hendrik Johannes (Bloemfontein: Central University of Technology, Free State, 2000)
There is a need to identify differences between three-dimentional objects that seem identical to the naked eye. The ability to compare threedimentional objects will enable one to determine wear that occured on mechanical parts as well as to determine the accuracy by which a copy was fabricated, whether it was done by means of a mould or by a rapid proto typing process. A problem encountered when companng th ~_ee - dimensional data is, to digitize the data at the exact same relative points on both models in order to enable comparison of all the data points with their counterparts. This is the reason why comparison of geometric data, generated by existing scanning systems and saved III a neutral file format, IS bound to be complicated. By orientating the models with one another pnor to scanlllng, data recorded on the same relative positions can be compared. Orientation IS done by the user with the aid of orientation tools included in the software that was written. This software controls two scanning machines to record the data in order to display differences graphically and statistically.
Thesis
Keywords: Three dimensional imaging - Systems; Data structures (Computer Science); Generation of geometric forms